PENGEMBANGAN PENDIDIKAN ISLAM BERKEMAJUAN PERSPEKTIF MUHAMMADIYAH - Ismunandar Ismunandar (Edusoshum : Journal of Islamic Education and Social Humanities, 2021)
This paper discuses the development of advanced Islamic education in the perspective of Muhammadiyah. The concept of advanced Islam is an opportunity for the challenges of the times to strengthen the strength of Islamic education itself. Muhammadiyah is one of the Islamic socio-religious organizations in Indonesia that has the spirit of Islamic reform, including part of the modernist Islamic organization in Indonesia. Muhammadiyah brings progressing Islam which carries the mission of building an advanced society in various aspects of life, both in social, social, economic, educational, cultural and political life. Therefore, Muhammadiyah continues to make serious efforts and endeavors tirelessly to create a true Islamic society. This study aims to identify and develop the current advanced Islamic education patterns. This type of research is using the library research method (library research) with data sources in the form of scientific articles, books, policy documents and circulars, journals, and other sources that are library in nature. The data collected was then analyzed in depth with content analysis techniques (Content Analysis) and presented descriptively. The results of the study indicate that advanced Islamic education is needed to be applied in Indonesia. Because the challenges of globalization require expertise on all fronts in responding to the problems of life today. Advancing Islamic education in the perspective of Muhammadiyah is Islamic education that integrates science with Islam. Education that integrates religion in the life of a holistic blend formed between faith and modernity.